PERSEPSI ORANG TUA DAN GURU TENTANG BERMAIN DAN BELAJAR ANAK USIA DINI - yus, anita; ray, damaiwaty (Jurnal Tematik, 2018)
This paper is based on the results of quantitative descriptive research by exploring the parents ’and teachers’ perceptions of early childhood play and learning aims to find out the perceptions of parents and teachers about early childhood play and learning as well as differences in perceptions of both. The sample of this research is 64 children parents and 64 teachers in early childhood education institution of Medan City which determined by using random sampling technique. Parent and teacher perceptions data were collected using questionnaires and continued focus group discussions with limited samples. The data were analyzed with descriptive statistics to calculate the mean score, standard deviation and percentage and qualitative analysis to see perceptual tendency and continued with difference test with formula Ï‡2 to see difference of perception of parent and teacher and difference of parent perception based on education. The results of the analysis show that (1) the perception of parents and teachers on early childhood play and learning is in the moderate category with the tendency to play rather than learn, (2) there is no significant difference between parent and teacher perceptions about play and learning (3) there is a significant difference between the perceptions of parents with under-educated and upper-educated elderly parents on early childhood play and learning, and (4) there is a significant difference between teachers’ perceptions of play based on educational background.